Heusler compounds Go Nano - Meyer, Judith; Teichert, Niclas; Auge, Alexander; Wang, Changhai; Huetten, Andreas; Felser, Claudia (Springer Verlag, 2016)
This chapter is addressing the physical impact of ferromagnetic Heusler entities when approaching the nanoscale, e.g. as nanoparticles or as very small grains in magnetic shape Heusler alloys, on resulting magnetic as well as microstructural properties. Based on the soft magnetic behavior of Co2FeGa and Co2FeSi as two representatives of the full Heusler family their superparamagnetic potential is projected to applications in biotechnology. These applications can now be pictured due to the progress which has been made in synthesizing Heusler nanoparticles. Taken Co2FeGa as a candidate the chemical preparation avenue to achieve nanoparticles with reliable physical properties is demonstrated leading to a nanoparticular GMReffect. It is shown that magnetic nanoparticles can be embedded in agarose as a biogel when employing external magnetic fields so as to configure the nanoparticle arrangements for optimizing the GMR-effect. Possible consequences in case of a nanoparticular TMR-effect are pictured. The very small grain size in magnetic shape Heusler alloys is determining the austenite-martensite transformation in ultra-thin films which might play a major role for spintronic applications also bridging two research field in addition. The principle microstructural influences on the austenitemartensite transformation in thin films are discussed in terms of epitaxial growth, phase compatibility, crystal quality and size scale effects. Thereafter, details concerning the martensitic transformation in a film thickness range from 10 to 100nm are discussed for two off-stoichiometric NiMnSn Heusler compositions.
CRIS-Team Scopus Importer:2023-03-20